Nusinersen versus Sham Control in Infantile-Onset Spinal Muscular Atrophy - Richard S. Finkel; Eugenio Mercuri; Basil T. Darras; Anne M. Connolly; Nancy L. Kuntz; Janbernd Kirschner; Claudia A. Chiriboga; Kayoko Saito; Laurent Servais; Eduardo F. Tizzano; Haluk Topaloğlu; M. Tulinius; et al. (2017)
Spinal muscular atrophy is an autosomal recessive neuromuscular disorder that is caused by an insufficient level of survival motor neuron (SMN) protein. Nusinersen is an antisense oligonucleotide drug that modifies pre–messenger RNA splicing of the SMN2 gene and thus promotes increased production of full-length SMN protein.